Analisis Kebutuhan Dan Ketersediaan Ruang Parkir Pada Maxi Store Jalan Perintis Kemerdekaan - Novi Rangga (Paulus Civil Engineering Journal, 2025)
Many problems arise if parking arrangements are inadequate. At Maxi Store, parking arrangements are still done manually. Parking attendants are still used in managing vehicle parking to direct and supervise parked vehicles. An example of a problem that arises is the lack of arrangement of vehicles in the parking area, so that there are often empty spaces that cannot be occupied. This results in the parking lot not being able to accommodate vehicles optimally, which ultimately means vehicles cannot occupy the parking area. To confirm whether the parking space in the Maxi Store yard on Jalan Perintis Independen is available. This research uses a field survey as a data collection method. From the analysis of parking characteristics data at the Maxi Store, it was obtained that the total parking capacity for cars was 11 vehicles with a 90˚ parking pattern, while motorbikes accommodated 46 vehicles with a 90˚ parking pattern. It is known that the average volume of car parking is 92 vehicles and for motorbikes it is 269 vehicles. It was found that the average accumulation of car parking was 10 vehicles and for motorbikes it was 47 vehicles. And the average parking index for cars is 90.91%, and for motorbikes it is 102.90%.